Tocilizumab in systemic juvenile idiopathic arthritis in a real-world clinical setting: results from 1 year of postmarketing surveillance follow-up of 417 patients in Japan - Yokota, Shumpei; Itoh, Yasuhiko; Morio, Tomohiro; Origasa, Hideki; Sumitomo, Naokata; Tomobe, Minako; Tanaka, Kunihiko; Minota, Seiji (Annals of the rheumatic diseases, 2016)
ObjectivesTo evaluate the safety and effectiveness of tocilizumab (TCZ) in patients with systemic juvenile idiopathic arthritis (sJIA) in real-world clinical settings in Japan.MethodsPaediatric patients with sJIA initiating TCZ between April 2008 and February 2012 and those previously enrolled in clinical trials who initiated TCZ before April 2008 were enrolled in a Japanese registry surveillance programme. Safety and effectiveness parameters were collected for 52 weeks.ResultsOf 417 patients enrolled, mean age was 11.2 years and 48.0% were female. TCZ exposure was 407.0 patient-years (PYs). Baseline corticosteroid use was higher than in clinical trials. Rates of total adverse events (AEs) and serious AEs (SAEs) were 224.3/100 PYs and 54.5/100 PYs, respectively, with SAEs higher than previously reported. The most frequent AEs and SAEs were infections and infestations (69.8/100 PYs and 18.2/100 PYs, respectively). 74 serious infections occurred in 55 patients (18.2/100 PYs); higher than previously reported. 26 macrophage activation syndrome events were reported in 24 patients (6.4/100 PYs). Fever and rash symptoms improved from baseline to week 52 (54.6% to 5.6% and 43.0% to 5.6%, respectively). At 4 weeks, 8 weeks and 52 weeks, 90.5%, 96.2% and 99.0% of patients achieved normal C reactive protein levels (<0.3 mg/dL), respectively.ConclusionsThese first real-world data demonstrated that TCZ was well tolerated, with acceptable safety and effectiveness in patients with sJIA. Higher incidences of SAEs and serious infections may be due to differences, such as corticosteroid use and concomitant diseases, between patient populations enrolled in previously reported clinical trials and this study.